Relationship of Oral Health Literacy with Decision-making in Dental Treatment Planning among Urban Population of Lahore: Oral Health Literacy & dental treatment planning - Alamgir, Wajiha; Tariq, Shanzay; Haider, Adeel; Jabbar, Uzma; Sarwar, Arfa; Abrar, Faheem (Pakistan Journal of Health Sciences, 2022)
In clinical settings, dentists frequently come across patients with variable oral health literacy, and they are not always able to tell which patients might comprehend with health-related explanations and instructions. Objective: To calculate oral health literacy level of patients reporting for dental treatment and correlation of the aforementioned with patients’ decision-making capacity regarding dental treatment. Methods: A quantitative cross-sectional study was conducted with a pilot study on 60 patients in University Dental Hospital, University of Lahore through non-probability purposive sampling technique. Sample of 200 patients was collected over a period of five months (June 2022-October 2022). Data were analyzed using SPSS version 25. Study was divided into two phases; in Phase I, REALD-30 scale was used. Phase-II involved individuals scoring 11-30 points on REALD-30 scale and who had to complete a self-administered 5-point Likert scale questionnaire with eleven closed-ended items in order to determine their level of decision-making. Results: Study revealed that there was significant association between Oral Health Literacy Level with getting prior information concerning dental issue (p=0.032), ability to appraise the decided treatment plan (p=0.033) and opinion regarding follow up visits (p=0.026). Conclusions: The results of the current study revealed a tenuous link between education, employment position, oral health literacy, and decision-making regarding dental treatment strategy. Effective patient-dentist communication generates strong link between the two leading to compliance of patients with treatment plan suggested by experts